Answer:
(gºf)(0) is 6
Explanation:
It is a composition of functions problem, where
(gºf) = g(f(x)) is the composition of the functions g(x) and f(x). (gºf)(0) is the composition of the functions at the point x = 0. First, we find that function that is the g composite of x, then we replace x by 0.
g(4), for example, is g when x = 4, right? So g(4) = 4.
So,
g(f(x)) is going to represent g when x = f(x). x = f(x) when x = 2x + 6, so:
g(f(x)) = g(2x+6) = 2x + 6
We have that
g(f(x)) = gºf(x) = 2x + 6
Now, we just have to find the value of the function at x = 0. So
gºf(0) = 2(0) + 6 = 0 + 6 = 6.
(gºf)(0) is 6